The Difference between Standard American English Pronunciation and the Interlanguage of English Department Students of the Class of 2015 at Andalas University - Rinjani Kusuma Putri; Zulfakhri Dt. Majo Datuk (English Department, Faculty of Humanities, Andalas University, 2020)
This study discusses (1) the differences between the students’ interlanguage and standard American English pronunciation, and (2) the patterns of phonetic shift from the Standard American English into the students’ Interlanguage Pronunciation. The participants of this research were English Department students, the year of 2015, at Andalas University and were selected by using stratified random sampling with academic achievement as the criteria in choosing the sample. The data were collected by using picture description task and analyzed by using Markedness Differential Hypothesis (MDH) by Eckman (1977) where the markedness relation among the sounds were found by using Markedness Hierarchy by Lombardi (1995, 1998). The result of the analysis showed that the most frequent errors that the participants made were the pronunciation of [ð], [θ], and [v] where the participants replaced [ð] with [d],[θ] with [t], and [v] with [f]. The difficulties of the participants were mostly in line with Eckman’s MDH.